1980
DOI: 10.1073/pnas.77.5.3067
|View full text |Cite
|
Sign up to set email alerts
|

Independence of the positive inotropic effect of ouabain from the inhibition of the heart Na+/K+ pump.

Abstract: Isolated left atria from guinea pigs were stimulated at 3.3 Hz and bathed at 30'C in Tyrode's solution containing 6 mM KCL. After equilibration, this solution was replaced by a low-K solution or by Tyrode's solution containing ouabain or dihydroouabain. These treatments evoked an increase in the contractility of the atria. The time to peak increase was about 30 min, and the inotropic effect was sustained for at least 40 min. After 30 min, 42K was added to the bathing solution in order to estimate the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…However, in other tissues, such as sheep Purkinje fibres (Hart, Noble & Shimoni, 1983) and guinea-pig atria (Godfraind & Ghysel-Burton, 1980), it has been proposed that the inotropic effect of ouabain is due to more than one mechanism and the present observations on rat heart are in agreement with this theory.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, in other tissues, such as sheep Purkinje fibres (Hart, Noble & Shimoni, 1983) and guinea-pig atria (Godfraind & Ghysel-Burton, 1980), it has been proposed that the inotropic effect of ouabain is due to more than one mechanism and the present observations on rat heart are in agreement with this theory.…”
Section: Discussionsupporting
confidence: 81%
“…This is in agreement with the existence of an antagonism exerted by dihydroouabain to the ouabain inotropic effect. It has been proposed that the ouabain inotropic effect is due to the inhibition of the Na+, K+-pump (Repke, 1963;Langer, 1977), but this theory is not universally accepted (Ghysel-Burton & Godfraind, 1980;Noble, 1980;. In rat ventricles, the range of concentrations at which ouabain inhibits the pump appears to be higher than 10-5 M according to Erdmann, Philipp & Scholz (1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RuizCeretti et al (10) showed that a similar effect occurs in rabbit ventricles. Godfraind (27)(28)(29)(30) showed that low concentrations of ouabain and digoxin that increase contractile force also stimulate 42K uptake by and Na content of guinea pig atria. In sheep Purkinje fibers, 0.1 M ouabain produced depletion of cleft potassium as judged from reversal potential for the iK2 current, again suggesting pump stimulation (20 The indices of Na-K pumilp f'unctioll examined in this study are a, and a'.…”
Section: Discussionmentioning
confidence: 99%
“…Cats weighing 1.5-3.0 kg were anesthetized with sodium pentobarbital, 30 mg/kg i.p. The hearts were rapidly removed and immersed in Tyrode's solution of the following composition in mM: NaCl, 135.4; KC1, 5.4; NaH2PO4, 1.8; CaCl2, 2.7; MgCl2, 0.5; NaHCO3, 18; and dextrose, 5.5.…”
Section: Methodsmentioning
confidence: 99%